The Dismantling of Family Farming Policies in Brazil and Argentina - Eric Sabourin; Clara Craviotti; Carolina Milhorance (International Review of Public Policy)
This article examines the recent processes of dismantling public policies oriented to promote or regulate family farming in Latin America. It addresses two main questions: How and why were these policies dismantled? Drawing on Bauer et al.’s (2012) analytical framework, the article examines the modalities and stages of the process of dismantling family farming policy instruments in Brazil and Argentina. Likewise, it analyzes the process’s causes by delving into structural, contextual and institutional factors. It adopts this framework, originally developed for social policies in Europe, to analyze rural policies in Latin America. From a theoretical point of view, the study suggests the importance of analyzing the resilience of policies and the mechanisms and strategies of resistance to governmental shifts as these affect the degree and direction that the process of dismantling may take.